2021
DOI: 10.3390/diagnostics11112051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Elastographic and Electromyographic of Pelvic Floor Muscles in Postmenopausal Women with Stress Urinary Incontinence Symptoms

Abstract: Background. Shear wave elastography is an effective method for studying the condition of various musculoskeletal soft tissues. The primary aim of this study was the objective elastographic and electromyographic assessment of the pelvic floor during the rest and contraction of the pelvic floor muscles (PFM) in postmenopausal women. Methods. This was a prospective observational study that was carried out at the University Hospital in Wroclaw, Poland, between January 2017 and December 2019. Patients. The target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In line with our results, Verelst et al 30 observed an increase in active PF stiffness in women with UI, more pronounced with increasing parity, thus reinforcing the possible influence of vaginal birth and UI on the MMP of the PF. The increased tone and stiffness found in the uni/multiparous women with UI in our study could be explained by a possible altered motor control of the musculature 31,32 and the changes of PF connective tissue secondary to the combination of vaginal birth and UI, 33 which may prevent the generation of sufficient force to maintain continence under stress. 30 It is known that hypertonia (increased muscle tension at rest) can prevent proper sliding of actin and myosin myofilaments, responsible for muscle contraction and relaxation, and hinder the generation of muscle strength and endurance.…”
Section: Discussionmentioning
confidence: 64%
“…In line with our results, Verelst et al 30 observed an increase in active PF stiffness in women with UI, more pronounced with increasing parity, thus reinforcing the possible influence of vaginal birth and UI on the MMP of the PF. The increased tone and stiffness found in the uni/multiparous women with UI in our study could be explained by a possible altered motor control of the musculature 31,32 and the changes of PF connective tissue secondary to the combination of vaginal birth and UI, 33 which may prevent the generation of sufficient force to maintain continence under stress. 30 It is known that hypertonia (increased muscle tension at rest) can prevent proper sliding of actin and myosin myofilaments, responsible for muscle contraction and relaxation, and hinder the generation of muscle strength and endurance.…”
Section: Discussionmentioning
confidence: 64%
“…At present, specific functional information of PFM can be obtained using various detection systems. Ultrasound is a well-used tool to check the disease status [ 8 , 9 , 10 ]. Magnetic resonance imaging technology can also be applied to detect the symmetry and coordination of PFM [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Handheld devices are used for measuring the mechanical properties of PFM [ 14 ]. The surface electromyogram (sEMG) is the main technology for evaluating the PFM activity status in clinic [ 8 , 15 , 16 , 17 ]. However, traditional rigid dual-channel probe is used to collect the sEMG signal of PFM, which cannot characterize the complex PFM structure because it can only collect the sEMG signal of integral PFM rather than the detailed information of the muscles [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been used to evaluate the mechanical properties of muscles and to detect tissue elasticity 20,21 . It has also been used to assess the elastic properties of PFM in non-pregnant women in neutral and stretched positions 19 .…”
Section: Introductionmentioning
confidence: 99%